The Brush That Has Delineated the Sugar Landscape In Tucumán And In São Paulo: The Sugar Industry In Rodríguez Marquina, and J. Picard’s Memoirs - Meira, Roberta Barros; Campi, Daniel (Esboços: histories in global contexts, 2023)
The reports and memoirs produced by technicians and civil servants from the statistical offices on the subject of the sugar industry bring to light the impact of agronomic sciences at the beginning of the 19th century and the first quarter of the 20th century. The imbricated transnational network of knowledge circulation that united the different agrarian spaces was an important factor in rethinking the old techniques of sugar production and sugarcane cultivation. To the clashes on international markets or for the internal consumption of each country came the ideas of agricultural progress that were increasingly linked to science. This article aims to discuss the circulation of knowledge, environmental problems, projects that sought to rationalize the countryside and the tensions between traditional and modern ways of producing sugar in the view of two actors who experienced changes in sugar landscapes in Brazil and in Argentina.